Penanaman Nilai-Nilai Pancasila Pada Masyarakat Daerah Perbatasan Indonesia-Malaysia (Desa Kumba, Kecamatan Jagoi Babang) - Dina Anika Marhayani; Dyah Indraswati (Jurnal Rontal Keilmuan Pancasila dan Kewarganegaraan, 2020)
AbstractThis research aims to study the planting of Pancasila values in the Indonesia-Malaysia border area (Jagoi Babang District). This type of research used in this research is qualitative research with case study research. The sample in this study were teenagers seen 16-17 years who succeeded in 6 people. The research site is in the Kumba Village, Jagoi Babang District, Bengkayang Regency, West Kalimantan Province. Data collection methods in this study used observation and interviews. Data analysis techniques in this study used an interactive model. The results showed that there were still many experiments in instilling the values of Pancasila in adolescents in Kumba Village, Jagoi Babang District. Pancasila is only limited to the knowledge that has not been realized in everyday life. This research is expected to make the youth community in Kumba Village practice the values of Pancasila in their daily lives. Keywords: planting, Pancasila values, Indonesian borders